Studies on the mineral nutrition of the rice plant: XX. uptake of micronutrients by varieties IAC-164 and IAC-165 during the life cycle - Malavolta, E.; Vecchiato, A.B.; Medeiros, A.C.S.; Takahashi, H.W.; Kliemann, H.J.; Azevedo, J.A.; Thomazi, M.D.; Genú, P.J.C.; Leão, S.R.F.; Cabral, C.P. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1982)
Rice plants were grown in nutrient solution till the end of their life cycle. At given stages of development plant samples harvested for the determination of dry matter and micronutrient contents in the various organs. The following conclusions were drawn: only Fe accumulation showed some degree of positive relation with dry matter production; the pattern of distribution of the elements among the plant parts was essentially the same, for both varieties; B, Cu and Fe tend to concentrate in the root system; no clear cut pattern of variation in leaf composition could be described throughout the plant life cycle; maximum rate of uptake took place between full tillering and panicle formation.